Teachers' Implicit Attitudes Toward Students From Different Social Groups: A Meta-Analysis - Pit-ten Cate, Ineke M.; Glock, Sabine (Frontiers in Psychology, 2019)
Teachers´ attitudes toward their students have been associated with differential teachers´ expectations and, in turn, with students´ educational pathways. Theories of social cognition can explain the link between attitudes and behavior. In this regard, the distinction between implicit and explicit attitudes is worth to be considered, whereby implicit attitudes are automatically activated when the attitude object is present and guide automatic behavior. In contrast, explicit attitudes infer deliberation and reflection, hence affecting controlled behavior. As teachers often are required to act immediately in situations that do not allow for thoughtful reflection due to time restraints, teachers´ implicit attitudes concerning different student groups with shared characteristics, such as gender or ethnicity, may be especially important when considering teachers´ behavior in relation to students´ educational pathways. This notion is reflected by an increased interest in adopting implicit methodology in the educational domain. Over the last 10 years, several studies have been conducted in different countries, involving in- and preservice teachers and investigating their attitudes toward different student groups. Estimates of effects have varied and may be affected by sampling bias. To systematically review and integrate data from different studies, this meta-analysis focuses on teachers´ implicit attitudes. Following the systematic search of the database and initial screening, 43 articles were identified from which 22, describing 34 studies, were retained for the meta-analysis after further inspection. First analyses revealed an estimated average effect size of 0.56 for implicit attitudes in favor of non-marginalized groups. As there was a large extent of heterogeneity between studies, several moderator variables, were investigated. Results showed that the employed implicit measure and stimulus materials as well as the student target group affected the effect sizes. Low or non-significant relationships were reported between implicit and explicit attitudes. Findings are discussed in terms of theory and future research.